Synthesis and characterization of aryl-substituted BODIPY dyes displaying distinct solvatochromic singlet oxygen photosensitization efficiencies - Gonçalves, Raquel C. R. (2021)
Three BODIPY derivatives substituted at meso position by aryl (phenyl or N,N-dimethylaminonaphthyl) groups and functionalized at position 2 with electron-withdrawing formyl or electron deficient benzimidazole heterocycle were synthesized and completely characterized by the usual spectroscopic techniques. A comprehensive photophysical study showed a remarkable enhancement of the singlet oxygen sensitization quantum yield for meso-substituted dimethylaminonaphthyl BODIPY with the decrease of the dielectric constant of the solvent (0.02–0.04 for dimethylsulfoxide vs. 0.84 in toluene). In toluene the triplet state formation for the aminonaphthyl substituted BODIPY's was found to be mediated by the intramolecular charge transfer state (ICT), whereas in polar solvents triplet state formation is hindered by fast recombination of the ICT state. Pump-probe transient absorption spectroscopy was used to characterize the photoinduced dynamics of the BODIPY derivatives from the femtosecond to the nanosecond time scale.